The SCP2‐thiolase‐like protein (SLP) of Trypanosoma brucei is an enzyme involved in lipid metabolism. Issue 8 (9th May 2016) - Harijan, Rajesh K.; Mazet, Muriel; Kiema, Tiila R.; Bouyssou, Guillaume; Alexson, Stefan E. H.; Bergmann, Ulrich; Moreau, Patrick; Michels, Paul A. M.; Bringaud, Frédéric; Wierenga, Rik K.
ABSTRACT: Bioinformatics studies have shown that the genomes of trypanosomatid species each encode one SCP2‐thiolase‐like protein (SLP), which is characterized by having the YDCF thiolase sequence fingerprint of the Cβ2‐Cα2 loop. SLPs are only encoded by the genomes of these parasitic protists and not by those of mammals, including human. Deletion of the Trypanosoma brucei SLP gene (TbSLP) increases the doubling time of procyclic T. brucei and causes a 5‐fold reduction of de novo sterol biosynthesis from glucose‐ and acetate‐derived acetyl‐CoA. Fluorescence analyses of EGFP‐tagged TbSLP expressed in the parasite located the TbSLP in the mitochondrion. The crystal structure of TbSLP (refined at 1.75 Å resolution) confirms that TbSLP has the canonical dimeric thiolase fold. In addition, the structures of the TbSLP‐acetoacetyl‐CoA (1.90 Å) and TbSLP‐malonyl‐CoA (2.30 Å) complexes reveal that the two oxyanion holes of the thiolase active site are preserved. TbSLP binds malonyl‐CoA tightly ( K d 90 µM), acetoacetyl‐CoA moderately ( K d 0.9 m M ) and acetyl‐CoA and CoA very weakly. TbSLP possesses low malonyl‐CoA decarboxylase activity. Altogether, the data show that TbSLP is a mitochondrial enzyme involved in lipid metabolism. Proteins 2016; 84:1075–1096. © 2016 Wiley Periodicals, Inc.